Description of Women's Knowledge about Menopause Complaints in Simbolon Village Padang Bolak District - Harahap, Ica Fauziah; Nurhidayah Harahap (PT Inovasi Pratama Internasional, 2022)
Menopause is the last phase where a woman's menstrual bleeding stops completely. Menopausal syndrome is experienced by many women almost all over the world. In women who will experience menopause, they will experience symptoms or signs such as depressed mood, anxiety, decreased well-being and sleep disturbances. Factors causing menopause are caused by changes in the production of the hormones estrogen and progesterone, age at menarche, parity and contraception. The purpose of this study was to determine the knowledge of women about menopause complaints in Simbolon Village. This type of research is quantitative in nature using a descriptive research design. The population in this study were all women aged 45-55 years who lived in Simbolon Village totaling 56 people with a total sampling technique, where the entire population was used as the research sample. The results showed that the majority of respondents had sufficient knowledge about menopause complaints as many as 22 people (39.3%) and a minority of less knowledge as many as 16 people (28.6%). Respondents are expected to actively seek information about complaints during menopause.